Influences of Psychological Intervention on Negative Emotion, Cancer-Related Fatigue and Level of Hope in Lung Cancer Chemotherapy Patients Based on the PERMA Framework - Min Tu; Fan Wang; Sanying Shen; Hui Wang; Jing Feng (Tehran University of Medical Sciences, 2021)
Background: Psychological status is a decisive factor for regulating the lung cancer chemotherapy patients' levels of fatigue and hope. Using the PERMA (Positive Emotion, Engagement, Relationships, Meaning, and Accomplishment) framework. We aimed to explore the influences of the psychological intervention on the patients' negative emotion, cancer-related fatigue, and level of hope. Method: A total of 100 lung cancer chemotherapy patients admitted in Wuhan No.4 Hospital, China, from Jan 2018 to Aug 2019 were enrolled as research objects divided into the control group and observation group. Positive psychological intervention using the PERMA framework was given to the observation group. The scores of Post-Traumatic Growth Inventory (PTGI), Self-rating Anxiety Scale (SAS), Self-rating Depression Scale (SDS), Cancer Fatigue Scale (CFS), and Herth Hope Index (HHI) were evaluated and compared in the two groups. Results: After the intervention, PTGI score in the observation group is higher than that in the control group, whereas the SAS and SDS scores are lower in the observation group than in the control group, and the differences are statistically significant (P<0.05). Score of each CFS dimension and total CFS score in the observation group are all lower than those in the control group, with statistically significant differences (P<0.05). Score of each HHI dimension and total HHI score are higher than those in the control group, and the differences are statistically significant (P<0.05). Conclusion: Positive psychological intervention using the PERMA framework can improve the emotional and fatigue state of lung cancer chemotherapy patients and elevate their level of hope.